Circularly polarized antenna array based on hybrid couplers for 5G devices - Tan Minh Cao; Thao Hoang Thi Phuong; Thi Duyen Bui (Institute of Advanced Engineering and Science, 2021)
This paper depicts a wideband circularly polarized (CP) antenna for 5G devices. The antenna array has a 3D structure including four simple printed dipole elements with directional radiations, high gain, and high efficiency. It achieves a CP by using the sequential rotation (SR) feeding based on 90°-3dB hybrid couplers in the proposed feeding network. The antenna array bandwidth is wide, 26.7%, with an operating frequency band from 3.35 GHz to 4.35 GHz. The antenna achieves a high peak gain of 10.73 dBi and high efficiency of 93.75%. Besides, the antenna gain is stable over the operating bandwidth (BW). At the centre operating frequency of 3.75 GHz, the angle of circular polarization is 51°. The antenna is designed and fabricated on the Rogers 4003 C substrate. The measured S11 is well matching with the simulation results. With the above characteristics, the proposed antenna can be a suitable candidate for 5G devices.